Strategi Kepolisian Dalam Penanganan Unjuk Rasa Menyampaikan Pendapat Dimuka Umum Kota Makassar - Ayuni, Nur; Umar, Firman; Akbal, Muhammad (Phinisi Integration Review, 2021)
The study aims to discover: (1) the dynamics of demonstrations in expressing opinions publicly in Makassar City; (2) the Police strategies in handling demonstrations in expressing opinions publicly in Makassar City; Â and (3) the determinant factors in handling demonstration in expressing opinions publicly in Makassar City. This study uses qualitative research with a descriptive approach. Based on the source, the types of data used are primary and secondary data. The primary data were obtained through interview with members of the Polrestabes Police from the Sat Sabhara Unit, the Sat Intelkam Unit, and the Brimob Unit as well as documentation. While the secondary data were obtained from various literatures such as books, laws, and other related sources. The data process and data presentation were conducted descriptively. The results of the study show that: (1) the dynamics of demonstration in expressing opinions publicly in Makassar City showed by the demonstration activities that occurred in Makassar City from January to December 2019 were fluctuating, (2) the Police's strategies in handling demonstration in expressing opinions publicly in Makassar city is based on the Regulation of the Chief of Police Number 1 of 2009 concerning the Use of Force in Police Actions, and (3) the determinant factors in handling demonstration in expressing opinions publicly in Makassar city are two, namely the supporting and inhibiting factors. The supporting factors are: a) there is physical and mental readiness from the police, b) there is good cooperation between the police, c) there is a quick response from the demonstration activity agency; whereas the inhibiting factors are: a) permitting does not comply with administrative requirements, b) presence of provocateurs, c) making sudden requests for permits, and d) lack of communication between protesters and police officers.